A novel region selection approach of SVPWM for a three-level NPC inverter used in electric vehicle - Roy, Debanjan; Kumar, Sanatan; Singh, Madhu (Institute of Advanced Engineering and Science, 2019)
This paper confers an investigation of a space vector modulation based control strategy of induction motor using a three-level inverter for electric vehicle application. The proposed controller uses a simple v/f control with a novel SVPWM technique. A new method for region selection of SVPWM for a multilevel inverter is implemented for the closed-loop system. Previously the region selection procedure was not considered by most of the researcher in the literature for developing the PWM algorithm. This approach is based on some algebraic equations. The remarkable point here is that it is identical to all the remaining sectors. Hence calculation complexity reduces by making it a simpler implementation. This method can be applied to any number of levels. The potency of the proposed controller is validated through the MATLAB/SIMULINK environment. The performance of the overall system is inspected through transient and steady-state analysis. The neutral point balance of the 3L NPC inverter is established by adopting proper switching sequences.